Analisis Pengaruh Luas Lahan Dan Teknologi Pertanian Terhadap Produksi Padi Di Indonesia (Menggunakan Data Indonesia Family Life Survey Gelombang 5) - Setianingsih, Eni; Nursalim, Nursalim; Alamin, Rahmatan Lil (STIE Jambatan Bulan, 2025)
This study aims to determine the effect of land area and agricultural technology on rice production in Indonesia. The research method employed is quantitative data analysis, which examines the impact of land area and agrarian technology on rice production in Indonesia. The analytical tool used is regression analysis, utilizing Stata 14 software. This study also employs the Ordinary Least Squares (OLS) regression analysis, as the data used in this research is cross-sectional data from the Indonesia Family Life Survey (IFLS) Wave 5 (2014), which is used to identify the influence of land area and agricultural technology on rice production. The results indicate that land area significantly affects rice production in Indonesia. A 1 percent increase in land area leads to a 0.37 percent increase in yield. Additionally, the application of agricultural technology through irrigation systems, whether from rainwater sources, well or pump irrigation, or other water sources, also significantly affects rice production. Moreover, using agricultural technology through rice seed varieties significantly enhances harvest yields, although the white glutinous rice variety does not show a significant effect.